Relationship Of Milk Production, Milk Expected Progeny Difference, And Calf Weaning Weight In Angus And Simmental Cow-Calf Pairs - Marston, Twig T. (Kansas State University, 1997)
Reproductive efficiency and weaning weight are traits that directly affect the profitability of a beef cow herd. Milk production directly affects these traits, thus indirectly influencing the profitability of cow/calf operations. The ability to predict the milking potential of an individual beef cow or a herd of beef cows can be used by producers to optimize the potential for profit from their operations. Milk production (a part of maternal ability of beef cattle) is a moderately heritable quantitative trait with moderate variation and indirect economic valμe (Van Vleck, et al., 1987). The relationship between milk production and calf preweaning growth, as expressed by weaning weight has been evaluated in many studies. Optimum milk production is a biological objective that is heavily dependent upon the factors of genetic ability, feed resources, and marketing situations (Ritchie, 1982). Therefore, producers need selection tools available to manipulate and manage the level of milk production in their cow herds. Prior to the development of National Cattle Evaluation (NCE) programs reported by breed associations, the only means of predicting milking ability was within herd comparison of weaning weights. Through NCE programs, milk expected progeny differences (EPDs ), provide comparisons of progeny genetic potential expressed in units of calf weaning weight, to predict the milking potential of progeny. The following literature review examines the characteristics of lactation curves, the techniques used to measure milk production, the factors that affect beef cow milk production (both fluid and components), the prediction of milk production, the procedure used to calculate EPDs, and compare EPDs to cattle performance.